2018
DOI: 10.1016/j.rgg.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Extremely magnesian olivine in igneous rocks

Abstract: Published data on extremely magnesian olivine (>96 mol.% forsterite) in igneous rocks were generalized and compared with data of new high-precision electron probe microanalyses of olivine from oxidized lavas of the Tolbachik Volcano (Kamchatka), chromitites from the Ray-Iz deposit (Russia), alkaline ultrabasic lavas from San Venanzo volcanoes (Italy), and skarns from the Kuh-i-Lal deposit (Tajikistan). All the found olivines resulted from low-temperature processes, such as subsurface oxidation, interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
1
19
0
1
Order By: Relevance
“…Further, the magmas derived from this partial melting process are incapable of crystallizing at shallow depths more refractory olivine (with Mg# higher than that of the corresponding residual olivine in the source regions) due to the Fe-Mg partitioning equilibrium [12,13]. Consequently, natural olivine with Mg# > 96 is not typical for any igneous rocks in general [14]. Natural olivine crystals with nearly pure forsteritic composition (with Mg# > 96) were sometimes found as phenocrysts in some basalts and kimberlites [15,16], as inclusions in chromites from some podiform chromitite [17], and as one of the metamorphic minerals in the contact zone between an igneous rock and a carbonate rock [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the magmas derived from this partial melting process are incapable of crystallizing at shallow depths more refractory olivine (with Mg# higher than that of the corresponding residual olivine in the source regions) due to the Fe-Mg partitioning equilibrium [12,13]. Consequently, natural olivine with Mg# > 96 is not typical for any igneous rocks in general [14]. Natural olivine crystals with nearly pure forsteritic composition (with Mg# > 96) were sometimes found as phenocrysts in some basalts and kimberlites [15,16], as inclusions in chromites from some podiform chromitite [17], and as one of the metamorphic minerals in the contact zone between an igneous rock and a carbonate rock [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated Mg# is believed to result from crystallization or equilibration in highly oxidized conditions. It has been shown that under high oxygen fugacity, magmatic olivine becomes almost pure forsterite due to trivalent Fe preventing substitution of Mg 2+ within the olivine crystal lattice [56,69]. Highly oxidized conditions of olivine-3 crystallization are consistent with low V/Sc ratios ( Figure 10B).…”
Section: Olivine-3: a Fingerprint Of A High-ca Potassic Magmamentioning
confidence: 73%
“…Elements, which distribution was mapped are specified on each inset. [56] and [57]. Specified on insets (A-L) are parameters, which are plotted on a certain chart, and total number of the analyses.…”
Section: Olivine Morphology and Chemistrymentioning
confidence: 99%
See 2 more Smart Citations